PATOGENISITAS CENDAWAN ENTOMOPATOGEN LECANICILLIUM LECANII (ZIMMERMAN) VIEGAS TERHADAP LARVA INSTAR III SPODOPTERA EXIGUA (LEPIDOPTERA: NOCTUIDAE) - Wahyuni, Dianita Tri; Isnawati, Isnawati; Suparno, Gatot (LenteraBio: Berkala Ilmiah Biologi, 2013)
This research aimed to describe the effect of the application of fungal L. lecanii concentration on mortality and time of death to the larvae of S. exigua. The method used were carried out an experimentally in the laboratorium and some parameters were analysed statistically using a single-factor completely randomized design with 6 concentration (105 conidia/ml, 106 conidia/ml, 107 conidia/ml, 108 conidia/ml, 109 conidia/ml and 0 conidia/ml) and 4 replications. The results showed that the application of various concentrations of an effect on mortality rates. At the concentration used was 105 conidia/ml, 106 conidia/ml, 107 conidia/ml, 108 conidia/ml and the concentration of 109 conidia/ml with a mortality rate respectively after application of 20%, 45%, 55%, 70 % and 75%. While the application of various concentrations of conidia showed that conidial concentration effect on the time of death. Each conidial concentration of 105?109 conidia/ml caused the death time is 212,4 hours, 187,2 hours, 159,6 hours, 141,6 hours and 126 hours.